2016
DOI: 10.4103/0973-1482.180610
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ciprofloxacin on the growth of B16F10 melanoma cells

Abstract: Ciprofloxacin seems to exhibit antitumor activity both in-vivo and in-vitro. This effect might be explained by several mechanisms such as directly inducing cancer cell death or altering the immune response through the modification of the normal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, the present analysis revealed that the expression of CDCA8 was significantly associated with lymph node metastasis. Regional lymph node metastases constitute the most common mode of initial presentation with metastatic melanoma ( 22 - 24 ). The updated 2009 AJCC melanoma staging system reported that, in the absence of nodal metastases, patients with intralymphatic metastases have a 5-year survival rate of only 69% ( 25 ), which may be one of the reasons CDCA8 affects the prognosis of cutaneous melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present analysis revealed that the expression of CDCA8 was significantly associated with lymph node metastasis. Regional lymph node metastases constitute the most common mode of initial presentation with metastatic melanoma ( 22 - 24 ). The updated 2009 AJCC melanoma staging system reported that, in the absence of nodal metastases, patients with intralymphatic metastases have a 5-year survival rate of only 69% ( 25 ), which may be one of the reasons CDCA8 affects the prognosis of cutaneous melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin has been extensively studied for its anticancer effects both in vitro and in vivo. Studies have shown that ciprofloxacin inhibits the cellular proliferation of melanoma cells B16F10, triple-negative breast cancer cells MDA-MB−231, pancreatic cancer cells Panc−1, non-small cell lung cancer cells A549, and hepatocellular carcinoma cells HepG2 [28,29,30,31]. Here, we report the chemosensitizing effects of ciprofloxacin by inhibiting the efflux function of ABCB1 transporter.…”
Section: Discussionmentioning
confidence: 74%
“…In comparison, the enzyme concentration in tumor cells is higher [10]. Several previous studies have already proven the efficacy of CPX in inhibiting hTOPO-II, leading to the anti-proliferative and cytotoxic activities of this molecule against several malignant cells [74,108]. Accordingly, we can expect that the CPX probe will be efficient and able to reach the desired location.…”
Section: Spectroscopic Parameters: 19 F-chemical Shifts (δ)mentioning
confidence: 95%